Teleexercise for geriatric patients with failed back surgery syndrome - Alizadeh, Reza; Anastasio, Albert Thomas; Shariat, Ardalan; Bethell, Mikhail; Hassanzadeh, Gholamreza (Frontiers in Public Health, 2023)
Introduction Failed back surgery syndrome (FBSS) is defined as back pain which either persists after attempted surgical intervention or originates after a spine surgery. There is a high risk of perioperative morbidity and a high likelihood of extensive revision surgery in geriatric patients with FBSS or post-laminectomy foraminal stenosis. Methods There is a need for less invasive methodologies for the treatment of FBSS, such as patient-tailored exercise training, with attention to the cost and special needs of the geriatric patients with FBSS. This commentary will provide some background regarding teleexercise (utilizing an internet-based platform for the provision of exercise-related care) for FBSS and will propose three exercises which are easy to administer over online-based platforms and can be the subject of future investigation. Results Given the documented benefits of regular rehabilitative exercises for patients with FBSS, the high cost of face-to-face services, and the need for infection mitigation in the wake of the COVID-19 Pandemic, teleexercise may be a practical and cost-beneficial method of exercise delivery, especially for geriatric patients with limitations in mobility and access to care. It should be noted that, prescription of these exercises should be done after face-to-face evaluation by the physician and careful evaluation for any “red flag” symptoms. Conclusion In this commentary, we will suggest three practical exercise training methodologies and discuss the benefits of teleexercise for geriatric patients with FBSS. Future research should aim to assess the efficacy of these exercises, especially when administered through telehealth platforms.